1991
DOI: 10.1104/pp.97.4.1271
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Chorismate Synthase from Euglena gracilis

Abstract: Chorismate synthase was purified 1200-fold from Euglena gracilis. The molecular mass of the native enzyme is in the range of 110 to 138 kilodaltons as judged by gel filtration. The molecular mass of the subunit was determined to be 41.7 kilodaltons by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Purified chorismate synthase is associated with an NADPH-dependent flavin mononucleotide reductase that provides in vivo the reduced flavin necessary for catalytic activity. In vitro, flavin reduction can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…microorganisms and plants) so far (for a review see [3]), there are considerable differences in enzyme organisation, as well as regulation, between organisms of different taxonomic groups. Chorismate synthases have been purified and characterized from the procaryotic microorganisms Escherichia coli [16,28] and Bacillus subtilis [9], the eucaryotic microorganisms Neurospora crassa [27,28] and Euglena gracilis [22], as well as from the higher plants Pisum sativum [17] and Corydalis sempervirens [23]. A comparative study of chorismate synthases from E. gracilis, C. sempervirens, E. coli and N. crassa showed that these enzymes were very similar in terms of cofactor specificity, kinetic and immunogenic properties, as well as their pH optima [22].…”
Section: Introductionmentioning
confidence: 99%
“…microorganisms and plants) so far (for a review see [3]), there are considerable differences in enzyme organisation, as well as regulation, between organisms of different taxonomic groups. Chorismate synthases have been purified and characterized from the procaryotic microorganisms Escherichia coli [16,28] and Bacillus subtilis [9], the eucaryotic microorganisms Neurospora crassa [27,28] and Euglena gracilis [22], as well as from the higher plants Pisum sativum [17] and Corydalis sempervirens [23]. A comparative study of chorismate synthases from E. gracilis, C. sempervirens, E. coli and N. crassa showed that these enzymes were very similar in terms of cofactor specificity, kinetic and immunogenic properties, as well as their pH optima [22].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced FMN is required for enzyme activity despite there being no overall reduction or oxidation in the conversion of EPSP to chorismate (15)(16)(17)(18)(19). The role of flavin is not yet clear but it appears to be directly involved in catalysis.…”
mentioning
confidence: 99%
“…Homonuclear 1 H decoupling experiments confirmed the connectivities between the resonances associated with positions 2-CH through to 5-CH. The double doublet 19 F resonance of (6S)-6-fluoro-EPSP at Ϫ174.35 ppm disappeared (Fig. 3, inset) giving rise to a new quartet at Ϫ111.39 ppm (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The chorismate synthases for which the reduced flavin has to be supplied exogenously are referred to as monofunctional, e.g. those from Escherichia coli and plants (3,(5)(6)(7)(8)(9), while chorismate synthases which possess the intrinsic ability to reduce the flavin at the expense of NADPH are referred to as being bifunctional, e.g. the Neurospora crassa enzyme (4,10,11).…”
mentioning
confidence: 99%